High Satisfaction Yet Decreased Activity 4 Years After Transphyseal ACL Reconstruction - Schmale, Gregory A. (Springer US, 2014)
BACKGROUND: ACL injuries in preteens and teens are common occurrences. Reconstruction is believed to be optimum treatment for those wishing to return to running, cutting, and jumping sports. Rates of reoperation, satisfaction, and long-term return to and maintenance of preinjury activity after ACL reconstruction in young athletes are important information for physicians, patients, and parents. QUESTIONS/PURPOSES: The purposes of this study were to address the following questions in this skeletally immature patient population undergoing ACL reconstruction: (1) What is the reinjury rate and the need for subsequent surgeries? (2) How do patient satisfaction and function as assessed by patient and physician correlate with return to sport? (3) What factors contribute to failure to return to preinjury activity levels? METHODS: This is a retrospective review of 29 patients who underwent transphyseal ACL reconstruction using soft tissue grafts passed through open physes and followed to skeletal maturity, and at least 2 years from their index surgery, who were invited and returned for a study interview and examination. Pre- and postinjury activity levels were assessed via the Tegner activity score, satisfaction was determined using a 10-point Likert scale, function was assessed via the Lysholm score and IKDC grade, and an open-ended questionnaire was used for explanations of changes in activity levels. Reoperations were classified as major or minor, determined from a review of the medical records conducted after interview and examination. RESULTS: At a minimum followup of 2 years (mean, 4 years; range, 2–8 years), four revision reconstructions and seven minor operations were performed for a reoperation rate of 11 of 29 (38%). Eight of 29 patients (28%) sustained contralateral ACL ruptures. The mean satisfaction score was 9 (range, 4–10) and mean Lysholm score was 91 (range, 61–100). Only 12 of 29 (41%) patients returned to and maintained their preinjury level of sport. High satisfaction correlated with return to prior level of sports, although there was no relationship between function and activity level. Reoperation on the index knee or contralateral ACL tear did not correlate with a change in activity level; rather, most patients who were less active indicated a change in interest with advancing age. CONCLUSIONS: Despite high satisfaction and function, less than 50% of patients maintained their preinjury level of play 4 years after ACL reconstruction. Satisfaction correlated significantly with knee function; highly satisfied patients were more likely to return to and maintain their prior level of participation in sports. Contributing factors to decreased activity include changes in lifestyle with increasing age. Reoperation did not correlate with lower activity scores or failure to return to sports. LEVEL OF EVIDENCE: Level IV, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.